Activity of chlorhexidine acetate in combination with fluconazole against suspensions and biofilms of Candida auris. Issue 1 (January 2022) - Hao, Weifeng; Wang, Yaxian; Xi, Yue; Yang, Zhe; Zhang, Heyu; Ge, Xuejun
Abstract: Objectives: As a newly emerging pathogen, Candida auri s has spread rapidly and caused a serious invasive infection. Candida auri s often appeared high resistance to classical antifungal drugs. Drug combination therapy is emerging as an effective and well-established strategy to relieve drug resistance problems. The objective of present work was to examine the activity of fluconazole in combination with chlorhexidine acetate against Candida auri s isolates. Methods: Antiplanktonic activity was studied using the EUCAST methodology and growth curve assay. Antibiofilm effectiveness was determined by the crystal violet method, checkerboard microdilution assay, scanning electron microscopy, and confocal laser scanning microscopy. Results: The results indicated that the 80% minimal inhibitory concentrations for fluconazole alone against Candida auris were 2–32 mg/L and for chlorhexidine acetate were 2–8 mg/L. The combination of fluconazole with chlorhexidine acetate exhibited synergism with the growth curve assay. In addition, the checkerboard microdilution assay presented that fluconazole was strongly synergistic with chlorhexidine acetate (sFICI <0.1875) in inhibiting the growth of Candida auris biofilms. The scanning electron microscopy and confocal laser scanning microscopy further exhibited the alteration of morphology of the cells and architecture of the biofilms. Conclusion: The combination therapy of fluconazole and chlorhexidine acetate provides a new potential strategy for the treatment of clinical Candida auris infection.